2017
DOI: 10.1007/s12272-017-0996-9
|View full text |Cite
|
Sign up to set email alerts
|

Nafamostat mesilate negatively regulates the metastasis of triple-negative breast cancer cells

Abstract: Triple-negative breast cancer (TNBC) lacking of oestrogen receptor, progesterone receptor, and epidermal growth factor receptor type 2 is a highly malignant disease which results in a poor prognosis and rare treatment options. Despite the use of conventional chemotherapy for TNBC tumours, resistance and short duration responses limit the treatment efficacy. Therefore, a need exists to develop a new chemotherapy for TNBC. The aim of this study was to examine the anti-cancer effects of nafamostat mesilate (NM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…To remove cellular debris, the cells were washed with 1 mL of phosphate buffered saline (PBS), placed in 2 mL of medium and then treated with 100 μM of CTZ, KCZ, FCZ, or ICZ. After 8-h incubation, the widths of the scratched line were measured and compared to that at 0 h ( Mander et al ., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To remove cellular debris, the cells were washed with 1 mL of phosphate buffered saline (PBS), placed in 2 mL of medium and then treated with 100 μM of CTZ, KCZ, FCZ, or ICZ. After 8-h incubation, the widths of the scratched line were measured and compared to that at 0 h ( Mander et al ., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The inserts were then air-dried and dissolved in 200 μL methanol, and 100 μL dye/solute mixture was transferred to a 96-well plate. The invasion ability of the cells was detected by measuring the absorbance at 540 nm using a Biotek ELISA reader (Fisher Scientific) ( Mander et al ., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular subtype of breast cancer based on receptor expression is helpful for prognosis and therapeutic response. Four common molecular subtypes are associated with breast cancers, Luminal A (ERα+/PgR+, HER2−), Luminal B (ERα+/PgR+, HER2+), HER2 (ERα−/PgR−, HER2+), and triple-negative (TN, ERα−/PgR−, HER2−) (2, 3). The luminal breast cancer subtypes are characterized by the expression of a set of ERα-related genes and represent approximately 75% of breast cancer patients in postmenopausal women (1).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, NM has been proven to downregulate the expression of both matrix metalloproteinase−2 (MMP-2) and−9, vascular endothelial growth factor (VEGF) and transforming growth factor beta 1 (TGF-β1), secreted by tumor cells in head and neck squamous cell carcinoma, and NM inhibits angiogenesis and tumor invasion (9). Furthermore, Mander et al reported the NM significantly inhibits proliferation, migration, and invasion in triple-negative breast cancer, which was identified both in vitro and in vivo (10). Moreover, NM reverses immune resistance induced by interferon-gamma (IFN-ɤ) as a method of increasing programmed cell death ligand-1 (PD-L1) expression in lung and pancreatic cancer (11).…”
Section: Introductionmentioning
confidence: 99%